Desenvolvimento de selo para melhores práticas de gestão no comércio segundo processos do pmbok - Silva, Vanessa Kolbe da (Universidade do Vale do Rio dos Sinos, 2016)
Brazilian traders face various adversities in the day to day to keep their establishments open and in full operation, and most of the difficulties come from the economic scenario, but mainly refers to the management carried out in the store. The present project aims to develop a methodology that establishes standards / metrics to be followed to obtain a seal of best management practices by small and medium-sized retailers in Porto Alegre. For this, it will be fundamental to establish a partnership with trade union or trade association reference in quality management systems, which will support the project and grant structure for execution, in addition to establishing partnerships with quality institutions to strengthen the program.
Keywords: Estabelecimentos aberto; Cenário econômico; Sindicato do comércio; Trade union; Economic scenario; Open establishments